2003
DOI: 10.1046/j.1365-2265.2003.01759.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growth hormone replacement therapy on adrenal androgen secretion in adult onset hypopituitarism

Abstract: This study shows that median serum DHEAS levels are significantly lower in GH-deficient patients, even those with intact ACTH reserve, than in aged-matched controls. GH replacement therapy is associated with a significant increase in mean serum DHEAS only in ACTH-sufficient patients. These findings are consistent with either (i) GH stimulation of adrenal androgen production in the permissive presence of ACTH or (ii) an inhibitory effect of GH on 11beta-HSD type 1 activity leading to enhanced cortisol clearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 54 publications
0
21
1
Order By: Relevance
“…Our results may be explained by the duration of treatment that is much longer than the 6 -8 week treatment previously reported (14,30). It has been argued that changes in cortisol-binding globulin might explain changes in circulating cortisol levels after GH replacement therapy, but results have been inconsistent (31,32).…”
Section: Discussioncontrasting
confidence: 46%
“…Our results may be explained by the duration of treatment that is much longer than the 6 -8 week treatment previously reported (14,30). It has been argued that changes in cortisol-binding globulin might explain changes in circulating cortisol levels after GH replacement therapy, but results have been inconsistent (31,32).…”
Section: Discussioncontrasting
confidence: 46%
“…Nevertheless, it has been suggested that, at least in rats, this effect may be indirectly mediated by Tinduced changes in growth hormone secretion [41]. Growth hormone administration has been observed to reduce plasma CBG levels in humans in some [42,43], but not in other studies [44,45]. It is thus possible that the postpubertal decrease in CBG levels observed in human males [46] may be mediated by raised growth hormone rather than T levels.…”
Section: Effect Of Testosteronementioning
confidence: 84%
“…This implicates that the activity of the 11 β -HSDs family, which interconvert 11-hydroxy and 11-keto steroids, could be another regulatory point in the activation or inactivation of 11-hydroxy and 11-keto androgens in the prostate [17]. The involvement of 11b-HSD in prostate physiology deserves future studies as it has already been shown to be crucial in several clinical conditions [18, 19]. …”
Section: Discussionmentioning
confidence: 99%